Tissue-resident memory T cells in the era of (Neo) adjuvant melanoma management - Plunkett, Kai R.; Armitage, Jesse D.; Inderjeeth, Andrisha-Jade; McDonnell, Alison M.; Waithman, Jason; Lau, Peter K. H. (Frontiers in Immunology, 2022)
Tissue-resident memory T (TRM) cells have emerged as key players in the immune control of melanoma. TRM are specialized cells that are identified by expression of tissue retention markers such as CD69, CD103 and CD49a with downregulation of egress molecules such as Sphingosine-1-Phosphate Receptor-1 (S1PR1) and the lymphoid homing receptor, CD62L. TRM have been shown to be integral in controlling infections such as herpes simplex virus (HSV), lymphocytic choriomeningitis virus (LCMV) and influenza. More recently, robust pre-clinical models have also demonstrated TRM are able to maintain melanoma in a dormant state without progression to macroscopic disease reminiscent of their ability to control viral infections. The discovery of the role these cells play in anti-melanoma immunity has coincided with the advent of immune checkpoint inhibitor (ICI) therapy which has revolutionized the treatment of cancers. ICIs that target programmed death protein-1 (PD-1) and cytotoxic T lymphocyte antigen-4 (CTLA-4) have led to substantial improvements in outcomes for patients with metastatic melanoma and have been rapidly employed to reduce recurrences in the resected stage III setting. While ICIs mediate anti-tumor activity via CD8+ T cells, the specific subsets that facilitate this response is unclear. TRM invariably exhibit high expression of immune checkpoints such as PD-1, CTLA-4 and lymphocyte activating gene-3 (LAG-3) which strongly implicates this CD8+ T cell subset as a crucial mediator of ICI activity. In this review, we present pre-clinical and translational studies that highlight the critical role of TRM in both immune control of primary melanoma and as the key CD8+ T cell subset that mediates anti-tumor activity of ICIs for the treatment of melanoma.